2009
DOI: 10.1590/s0066-782x2009001100007
|View full text |Cite
|
Sign up to set email alerts
|

Segurança da ecocardiografia transesofágica em adultos: estudo em um hospital multidisciplinar

Abstract: SummaryBackground: TEE is a semi-invasive tool broadly used and its utilization associated to sedatives drugs might to affect the procedure safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
1
Order By: Relevance
“…Cury et al addressed its safety,17 and Vieira et al assessed its utility for measuring left ventricular ejection fraction 18…”
Section: Methodsmentioning
confidence: 99%
“…Cury et al addressed its safety,17 and Vieira et al assessed its utility for measuring left ventricular ejection fraction 18…”
Section: Methodsmentioning
confidence: 99%
“…Por este motivo, a associação de depressores do sistema nervoso central em idosos ou em pacientes com insuficiência renal, cardíaca ou hepática deve ser monitorada, sendo indicado o uso de doses menores que as usuais. Os efeitos sobre o sistema cardiovascular são geralmente provocados por diminuição da resistência vascular periférica, depressão miocárdica e redução do débito cardíaco 36 .…”
Section: Frequência De Interações Medicamentosas Potenciaisunclassified
“…However, most of the 10,419 patients included in the study by Daniel Ideally, the hemodynamic parameters must be monitored during the TEE, as carried out by Cury et al 1 , who monitored the blood pressure and oxymetry. A previous study that monitored the blood pressure in 54 non-sedated patients, showed an increase in the blood pressure in 77% of the cases and a decrease in 22%.…”
mentioning
confidence: 99%
“…The authors concluded that dyspnea, coughing, odynophagia and hemoptysis symptoms after a TEE suggest the diagnosis of perforation and must be rapidly investigated 6 . Although the study by Cury et al 1 does not mention the use of anticoagulants, the literature suggests that the TEE is safe in patients using them. However, there has been a report of a case of esophageal hemorrhage in a patient that received thrombolytic therapy for the treatment of prosthesis thrombosis diagnosed by the TEE, suggesting that the thrombolytic therapy immediately after the TEE can be associated to a higher risk of bleeding 2 .…”
mentioning
confidence: 99%